2007
DOI: 10.3766/jaaa.18.2.7
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Health-Related Quality of Life and Hearing Aids: Final Report of the American Academy of Audiology Task Force on the Health-Related Quality of Life Benefits of Amplification in Adults

Abstract: This is the final report of the American Academy of Audiology Task Force on the Health-Related Quality of Life (HRQoL) Benefits of Amplification in Adults. A systematic review with meta-analysis examined evidence pertaining to the use of hearing aids for improving HRQoL for adults with sensorineural hearing loss (SNHL). Relevant search strings applied to the CENTRAL, CINAHL, Cochrane Reviews, ComDisDome, EBMR, and PubMed databases identified randomized controlled trial, quasi-experimental, and nonexperimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
287
0
16

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 388 publications
(312 citation statements)
references
References 99 publications
(80 reference statements)
9
287
0
16
Order By: Relevance
“…Our literature search suggested that many negative health and psychosocial consequences of poorly managed acquired hearing loss can be ameliorated by hearing aid use [20,62,63], providing a rationale for addressing hearing aid use. Two behavioural problems arose from this analysis: low levels of uptake of hearing healthcare and sub-optimal levels of hearing aid use once they are fitted.…”
Section: -Define the Problem In Behavioural Termsmentioning
confidence: 99%
“…Our literature search suggested that many negative health and psychosocial consequences of poorly managed acquired hearing loss can be ameliorated by hearing aid use [20,62,63], providing a rationale for addressing hearing aid use. Two behavioural problems arose from this analysis: low levels of uptake of hearing healthcare and sub-optimal levels of hearing aid use once they are fitted.…”
Section: -Define the Problem In Behavioural Termsmentioning
confidence: 99%
“…Segundo Assayag e Russo (2006), existem diferenças estatisticamente signifi cantes na avaliação subjetiva do benefício percebido por idosos quando comparadas às situações com e sem pró-teses auditivas, sendo que o benefício era mais bem percebido quando o indivíduo utilizava as próteses. Chisolm et al (2007) conduziram uma revisão de literatura sistemática através de uma meta-análise com o objetivo de buscar evidências no que diz respeito à relação entre o uso de próteses auditivas e a melhora na qualidade de vida de adultos com perda auditiva neurossensorial. Dos 171 resumos considerados relevantes e encontrados na pesquisa inicial, os autores destacaram 16 artigos que obedeciam a todos os critérios de inclusão pré-determinados no estudo.…”
Section: A Prótese Auditiva Como Ins-trumento De Inclusão Social E Seunclassified
“…Despite the benefits associated with hearing aid use (Chisolm et al, 2007), many adult hearing aid owners either do not complete rehabilitation programs or they use hearing aids less than the recommended four hours per day, with up to 30% abandoning use of hearing aids altogether Smeeth et al, 2002;Bertoli et al, 2009;Hartley et al, 2010;Hickson et al, 2010;Schneider et al, 2010;Dillon, 2012). Despite seeking aural rehabilitation, these people are living in the community with unaddressed hearing and communication difficulties.…”
Section: Introductionmentioning
confidence: 99%